Study of optimization techniques for optimal location of facts devices. Issue 1 (2nd January 2022) - Sharma, Sandeep; Sharen Ganesh, M. C.; Goyal, Jayesh; Lokesh,; Bhuyan, Tamanna
Abstract: The methods used for finding the best value out of the bulk amount of data available in a sample are known as optimization techniques. Different types of such techniques are used to make machines more efficient. FACTS devices play a vital role to compensate for the reactive power of the power system by means of improving the voltage profile of the system, as the reactive power of a power transmission system directly depends upon the magnitude of the voltage. The Newton-Raphson (NR) load flow method is used for IEEE 14 bus with its standard bus and branch data. The optimal size and location of G-UPFC found out by using ant colony optimization (ACO) is inserted in the different IEEE bus systems.